Phage Therapy: A Renewed Approach to Combat Antibiotic-Resistant Bacteria - Kortright, Kaitlyn E.; Chan, Benjamin K.; Koff, Jonathan L.; Turner, Paul E. (Cell host & microbe, 2019)
Phage therapy, long overshadowed by chemical antibiotics, is garnering renewed interest in Western medicine. This stems from the rise in frequency of multi-drug-resistant bacterial infections in humans. There also have been recent case reports of phage therapy demonstrating clinical utility in resolving these otherwise intractable infections. Nevertheless, bacteria can readily evolve phage resistance too, making it crucial for modern phage therapy to develop strategies to capitalize on this inevitability. Here, we review the history of phage therapy research. We compare and contrast phage therapy and chemical antibiotics, highlighting their potential synergies when used in combination. We also examine the use of animal models, case studies, and results from clinical trials. Throughout, we explore how the modern scientific community works to improve the reliability and success of phage therapy in the clinic and discuss how to properly evaluate the potential for phage therapy to combat antibiotic-resistant bacteria. In this Review, Kortright et al. present a historical overview of phage therapy and its usefulness in combatting antibiotic-resistant bacteria. The authors also highlight the advantages and limits of phage therapy through specific animal, clinical, and case studies and offer directions for future studies.